At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

If f(x) = x−6x^2 find (f(x + h) − f(x))/h

Sagot :

The value of  (f(x + h) − f(x))/h is 1 - 6h - 12x.

For any function, say f(x) = x + a, the value of f(x+b) = (x + b) + a or (x + b + a)

Here, we are given that

f(x) = x−6x^2

and we need to find the value of (f(x + h) − f(x))/h

Firstly,

f(x + h) = (x+h) - 6(x+h)^2

Now, f(x + h) − f(x) = (x+h) - 6(x+h)^2 - (x−6x^2)

= (x+h) - 6(x+h)^2 - x + 6x^2

= x - x + h - 6(x^2 + h^2 + 2xh) + 6x^2

= h - 6x^2 - 6h^2 - 12xh + 6x^2

=  h - 6x^2  + 6x^2 - 6h^2 - 12xh

= h - 6h^2 - 12xh

= h( 1- 6h - 12x)

Thus, (f(x + h) − f(x))/h = [h( 1- 6h - 12x)] / h

= 1 - 6h - 12x

Therefore, the value of  (f(x + h) − f(x))/h is 1 - 6h - 12x.

Learn more about functions here-

https://brainly.in/question/26266500

#SPJ9

We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.